The Personality Dynamics of the Main Character in the Novel Rara Mendut by Y.B. Mangunwijaya - Dewi Ulfah; Anwar Efendi (Universitas Negeri Makassar, 2026)
This study aims to analyze the personality dynamics of Rara Mendut, the main character in Y.B. Mangunwijaya’s novel Rara Mendut, through Sigmund Freud’s psychoanalytic perspective. It focuses on three interrelated aspects: life and death instincts, forms of anxiety, and ego defense mechanisms. This research uses a descriptive qualitative method with psychoanalytic literary criticism as the analytical approach. The primary data source is the novel Rara Mendut, while secondary data are obtained from relevant psychoanalytic and literary studies. Data were collected through close reading and note-taking techniques, then classified according to Freudian categories of instincts, realistic anxiety, neurotic anxiety, moral anxiety, and defense mechanisms. The findings show that Rara Mendut’s personality is shaped by the tension between Eros and Thanatos. Eros appears in her desire for love, freedom, dignity, and self-preservation, whereas Thanatos emerges in moments of despair, anger, and self-endangering resistance. Her anxiety arises from external domination, inner conflict, and moral pressure produced by feudal-patriarchal power. To manage these pressures, Rara Mendut employs several defense mechanisms, including rationalization, denial, regression, and sublimation. The study concludes that Rara Mendut is represented not merely as a rebellious woman, but as a psychologically complex subject negotiating desire, fear, honor, and power. The implication of this study is that Freudian psychoanalysis can enrich the interpretation of Indonesian literary characters by revealing the inner psychological consequences of social domination and by strengthening psychologically oriented approaches to gendered literary resistance studies.